Virtual health coaching for consumers: a persuasive systems design perspective. (1st January 2013) - Lehto, Tuomas; Oinas-Kukkonen, Harri; Pätiälä, Timo; Saarelma, Osmo
The lifestyle that people adopt has a direct impact on their health and well-being. On a global scale, lifestyle-related non-communicable chronic diseases (such as cardiovascular disease, diabetes and some forms of cancer) continue to increase and have become the leading causes of mortality. In recent years, there have been calls to action regarding the global burden of lifestyle-related non-communicable diseases. There is a demand for IT applications and systems that allow individuals' to manage their health and well-being and potentially alter their health-related behaviours. Persuasive technology has the potential to be in the forefront of novel health-related prevention services. Persuasive technologies are designed to induce and influence people to change their attitudes and behaviours. Behaviour change support systems (BCSSs) are at the heart of persuasive technology research and practice. The objective of this study is to investigate consumers' perceptions of an instantiation of a BCSS, called virtual health check and coaching, which is a non-clinical web-based system for personal lifestyle and health management. In the present study, we examine the consumers' insights through the persuasive systems design model. Implications for persuasive systems design are discussed.